Origin and Lineage Plasticity of Endogenous Lacrimal Gland Epithelial Stem/Progenitor Cells - Liana Basova (iScience, 2020)
Summary: The lacrimal gland (LG) is an exocrine organ responsible for the secretion of aqueous tear film. Regenerative and stem cell therapies that target LG repair are coming to the fore, although our understanding of LG cell lineage hierarchy is still incomplete. We utilize the analysis of label-retaining cells (LRCs) and genetic lineage tracing to define LG cell lineage hierarchy. Our study suggests that embryonic LG contains unique long-lived multipotent stem cells that give rise to all postnatal epithelial cell types. Following birth, lineages become established and the fate of progenitor cell descendants becomes restricted. However, some cell lineages retain plasticity after maturation and can trans-differentiate into other cell types upon injury. The demonstration that the LG contains progenitor cells with different levels of plasticity has profound implications for our understanding of LG gland function in homeostasis and disease and will be helpful for developing stem cell-based therapies in the future.